The Concept of Spiritual Leadership in Educational Institutions is Based on Maqashid Shari'ah - Arivatu Ni'mati Rahmatika; Samsul Ma'arif; Abd Wahid; Kamelia Evi Kusuma (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The purpose of this study is to find out a new concept of spiritual leadership based on Maqashid Syari'ah in educational institutions. This research uses a qualitative approach that uses literature studies and content analysis techniques. Spiritual leadership in educational institutions has three concepts, namely, assuming a leader has leadership traits since birth, group function is seen as leadership because the success or failure of a leader depends on how the group works and making concepts that are more advanced and better. This study also shows that leaders need to understand the importance of vision, altruistic love, and the expectations of members in leadership. The net result of the concept of spiritual leadership in educational institutions based on maqashid shari'ah must adjust to five forms of protection, namely, religious protection, protection of life, protection of property, protection of reason, and protection of lineage. From this form of protection, leadership in educational institutions will be more practical, structured, and consistent. After doing literature research by analyzing spiritual leadership based on maqashid shari’ah, it can be concluded that the content of the concept of spiritual leadership is by the protection in maqashid shari’ah